The Relationship Between Peers and Academic Procrastination Behavior of Grade X Students of SMA Negeri 1 Namorambe - Amalia Zamira; Dina Hidayati; NurAsyah, NurAsyah; Ika Sandra Dewi (Sean Institute, 2025)
Academic procrastination is a persistent problem among high school students, leading to reduced learning outcomes and lower academic achievement. Peer relationships are a key factor influencing procrastination, as adolescents often rely heavily on their peers for support, motivation, and identity. However, when peer interactions are not constructive, they may reinforce avoidance and task delays. At SMA Negeri 1 Namorambe, procrastination remains a challenge for many students, highlighting the need to better understand how peer relationships contribute to this behavior. Urgent attention to this issue is crucial to prevent negative impacts on students’ academic success and overall development. This study investigates the relationship between peer relationships and academic procrastination among students at SMA Negeri 1 Namorambe. Academic procrastination remains a prevalent issue in the school setting, often shaped by the social environment and habitual task delay. Employing a correlational research design, the study involved 60 students selected as the sample. Data were collected through a Likert-scale questionnaire and analyzed using Pearson’s Product Moment correlation with the aid of SPSS software. Findings revealed a strong and statistically significant positive correlation between peer relationships and academic procrastination (r = 0.710, p < 0.001). These results suggest that a higher intensity of peer interactions, when not positively directed, increases the likelihood of students postponing academic tasks. The study concludes that the quality of peer relationships plays a critical role in shaping academic behaviors, particularly procrastination. Consequently, fostering a supportive and constructive social environment within schools is essential to mitigate procrastination and enhance students’ academic achievement.